2004
DOI: 10.1124/mol.104.001495
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Interaction between the Dopamine D2 Receptor and Arrestin2 in Neostriatal Neurons

Abstract: Dopamine D2 receptor interactions with arrestins and arrestindependent internalization have been characterized using heterologously expressed D2 receptor and arrestins. The purpose of this study was to investigate D2 receptor interaction with endogenous arrestins. Arrestin2 and arrestin3 in striatal homogenates bound to the third cytoplasmic loop of the D2 receptor, and purified arrestin2 and arrestin3 bound to the second and third loops and C terminus of the D2 receptor, in a glutathione S-transferase pull-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 27 publications
(44 reference statements)
1
56
0
Order By: Relevance
“…Thus, all reported affinity measurements are in good agreement with the rest of the data, clearly indicating the multi-site nature of the arrestin-receptor interaction. Qualitative studies of direct arrestin binding to various elements of different receptors have implicated i3 of the m2 and m3 muscarinic, the α2A-adrenergic receptors (Wu et al, 1997), and the 5-HT2A receptor (Gelber et al, 1999), i3 and the C-terminus of delta-opioid and the C-terminus of kappa-opioid receptors (Cen et al, 2001b), as well as i2, i3, and the C-terminus of dopamine D2 (Macey et al, 2004) and D1 receptors (Macey et al, 2005). Where the binding of a combination of elements was tested (e.g., i3+C-terminus of the delta-opioid receptor (Cen et al, 2001b), it was found to be additive, suggesting that these elements bind to different sites on arrestin.…”
Section: Receptor Elements Implicated In Arrestin Bindingmentioning
confidence: 99%
“…Thus, all reported affinity measurements are in good agreement with the rest of the data, clearly indicating the multi-site nature of the arrestin-receptor interaction. Qualitative studies of direct arrestin binding to various elements of different receptors have implicated i3 of the m2 and m3 muscarinic, the α2A-adrenergic receptors (Wu et al, 1997), and the 5-HT2A receptor (Gelber et al, 1999), i3 and the C-terminus of delta-opioid and the C-terminus of kappa-opioid receptors (Cen et al, 2001b), as well as i2, i3, and the C-terminus of dopamine D2 (Macey et al, 2004) and D1 receptors (Macey et al, 2005). Where the binding of a combination of elements was tested (e.g., i3+C-terminus of the delta-opioid receptor (Cen et al, 2001b), it was found to be additive, suggesting that these elements bind to different sites on arrestin.…”
Section: Receptor Elements Implicated In Arrestin Bindingmentioning
confidence: 99%
“…For this reason, most antipsychotics currently in use are DRD2 antagonists. The function of DRD2 is determined by its levels on the plasma membrane (PM) (Lin et al, 2001Binda et al, 2002;Free et al, 2007;Kim et al, 2008a,b;Tirotta et al, 2008;Genedani et al, 2010), and DRD2 endocytosis plays an important role in its desensitization following DA stimulation (Kim et al, 2001;Jeanneteau et al, 2004;Kabbani et al, 2004;Macey et al, 2004;Namkung and Sibley, 2004;Sugiura et al, 2004;Bartlett et al, 2005;Genedani et al, 2005;Torvinen et al, 2005;Paspalas et al, 2006;Iizuka et al, 2007;Kim, 2008;Xiao et al, 2009;Celver et al, 2010;Shimokawa et al, 2010). However, the fate of DRD2 following DA-induced endocytosis remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the dopamine transporter protein, which regulates dopamine receptor activation, is known to be internalized into endosomes by a clathrindependent mechanism (Sorkina et al Gulledge and Jaffe 1998). Unlike Ntera-2 cells in culture, post-mortem rat brain is exposed to very high levels of released dopamine within a few minutes of death (Vulto et al 1988) and agonistinduced internalization of dopamine receptors can also be a very rapid process (Vickery and von Zastrow 1999; Macey et al 2004). It is possible that receptors have been internalized as a result of this process and this may partly explain why their endosomal location has not been described previously.…”
Section: Discussionmentioning
confidence: 99%